Dryland re warm-up on kids` swim start performance - Cuenca-Fernández, F.; Ruiz-Navarro, J. J.; Santos, C. C.; López-Belmonte, Ó.; Gay, A.; Arellano, R.; Stojanovic, N. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
The efficacy of warm-up methods in improving sporting performances has been extensively demonstrated (Bishop, 2003). Consequently, the effects of different warm-up techniques can vary based on factors such as the type, duration, and intensity of the exercise (Boullosa, 2021). Most studies have primarily focused on adult populations, however, the responses of young individuals in response to warm-up could be different due to varying muscle and physiological development. Children have lower muscle development and a lower percentage of fast fibers compared to adults (Dotan et al., 2012; Lexell et al., 1992). This percentage significantly increases from approximately 35% at the age of 5 years to approximately 50% at adulthod (Lexell et al., 1992). Furthermore, literature suggests that children have a reduced ability to voluntarily activate their type II motor units in comparison to adults since higher resistance may not significantly impact higher threshold motor units in children (Armatas et al., 2010; Dotan et al., 2013). Consequently, it is expected that children would be less responsive to intense or highload stimuli (Dotan et al., 2012; Lexell et al., 1992). In the context of swimming, a typical event consisting of multiple races, can span several hours from warm-up to competition. Specifically, the International Swimming Federation (FINA) rules stipulate that swimmers must enter the call room at least 20 minutes before the race for inspection by technical officials (www.fina.org). Besides, other factors such as delays in the competitive schedule or the time required for changing swimsuits can result in even longer transition periods. However, after a passive rest period of 15-20 minutes, muscle temperature can decrease rapidly, leading to adverse effects on performance (Bishop, 2003). For that reason, there has been significant interest among coaches and practitioners regarding the post-activation performance enhancements (PAPE) observed after incorporating bursts of voluntary activities during the transition phase between warm-up and competition (Cuenca-Fernández et al., 2022; Cuenca-Fernández et al., 2017). This approach, combined along with passive warm-up techniques, could help supplement or maintain the temperature increases and adaptations achieved through the in-water warm-up, particularly if there is an unavoidable delay between the warm-up and the actual task. Nevertheless, whether this strategy is beneficial for children remains to be established. Several studies, such as (Lätt et al., 2009) and (Arabatzi et al., 2014), have identified differences in physical development and performance during biological maturation, favouring better results for individuals with advanced maturity offset. Traditionally, PAPE responses have been attributed to a muscle-memory mechanism triggered in type II fibres due to recent high-intensity contractile activity (Rassier & Macintosh, 2000). Consequently, the lack of fast fibre development may compromise potential PAPE responses in children. However, current literature has questioned this theory, ascribing this acute phenomenon to increases in muscular temperature mediated by vascular, cardiorespiratory, and metabolic adaptations that occur after brief periods of voluntary exercise (Blazevich & Babault, 2019; Cuenca-Fernández et al., 2017). Hence, it is possible that PAPE responses may not solely be dependent on type II fibre stimulation, and could be induced in children through means of moderate-intensity activities. At this point, despite the existing evidence supporting the benefits of warm-up, devising effective and practical warm-up protocols for children can pose challenges due to the low day-to-day stability in their performance. For example, optimizing start performance is particularly crucial to success (Arellano et al., 2022). However, executing a successful start requires excellent motor coordination and control, making it a skilful performance (Vantorre et al., 2014). Furthermore, considering the time and space constraints in the call room, it becomes essential to design warm-up protocols that are feasible for children, since the available literature has primarily focused on warm-up routines for adults, which often incorporate sophisticated elements to induce highintensity stimulus (Cuenca-Fernández et al., 2022). Therefore, the objective of this study was to examine the influence of different warm-up routines on children`s swimming start (SS) performance and to elucidate potential underlying mechanisms. Our hypothesis was that a transition phase including dynamic activities would not cause fatigue but preserve the warm-up effects in children because of the PAPE effect